1985
DOI: 10.1038/ki.1985.160
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic analysis of the National Cooperative Dialysis Study (NCDS)

Abstract: The purpose of the NCDS was to determine the probability of clinical failure (PF) as a function of the level of dialysis and protein catabolic rate (pcr, g/kg/day). The level of dialysis prescribed in the NCDS was mechanistically defined as Kt/V (product of dialyzer urea clearance and treatment time divided by body urea volume), which exponentially determines decrease in BUN during dialysis and is also a mathematical analogue of pcr, BUN. Mechanistic analysis (MA) showed that PF was a discontinuous function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
652
3
16

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,239 publications
(683 citation statements)
references
References 0 publications
12
652
3
16
Order By: Relevance
“…The present NECOSAD analysis did not indicate that treatment duration itself may contribute to patient survival, which is in accordance with some other reports (1)(2)(3)7,33). However, an important drawback of the observational NECOSAD study is the restriction to treatment characteristics that are usually present in current dialysis practice.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The present NECOSAD analysis did not indicate that treatment duration itself may contribute to patient survival, which is in accordance with some other reports (1)(2)(3)7,33). However, an important drawback of the observational NECOSAD study is the restriction to treatment characteristics that are usually present in current dialysis practice.…”
Section: Discussionsupporting
confidence: 81%
“…The results of the National Cooperative Dialysis Study (NCDS) have led to the development of Kt/V urea to quantify the dialysis dose in ESRD patients who are treated with hemodialysis (HD) (1,2). In various studies, it was found that the Kt/V urea (or the urea reduction ratio as equivalent parameter) is an important predictor of morbidity and mortality (3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…With the exception of the National Cooperative Dialysis Study (23) and the HEMO Study (2), most efforts to determine optimal dialysis dose have come from examination of the relationship between dose and mortality in observational studies. One problem with analyzing datasets from observational studies is confounding of the dose of dialysis, be it urea reduction ratio, spKt/V, eKt/V, or stdKt/V, with body size.…”
Section: Discussionmentioning
confidence: 99%
“…Std K is multiplied by session time and divided by V to obtain Std Kt/V. Urea generation and V are calculated using traditional urea kinetic modeling (UKM) (13). The formula takes into account the number of treatments per week and urea rebound by using Daugirdas's eKt/V correction of the Sp Kt/V (14).…”
Section: Methodsmentioning
confidence: 99%